Utilisation of Idle Padi Lands in Negeri Sembilan - Hussein, Mohd Ariff; Thiran, Nyanen (1982)
The problem of idle padi land has attracted national attention in recent years. In Negeri Sembilan, I about 57 percent of the gazetted padi land are abandoned. The objectives of the study are to determine factors that contribute to the abandonment of padi land in the state and to suggest alternative uses of the land. The study shows that shortage of labour, low productivity of padi land, high off farm income, shortage of water and multiple land ownership are significant variables that influence farmer's decision to abandon their padi land. A linear programming analysis indicates that the idle padi land can be economically utilised for the cultivation of chillies, greenpeas, maize or sugar cane, and rearing of freshwater fish.